Growth in a changing climate: workshop report - Bird,J (Grantham Institute, Imperial College London, 2025)
This report summarises discussions held at two events exploring Growth in a Changing Climate held in June 2025.Economic growth is the Government’s number one mission. This will only be achieved if we think about growth in the context of a changing climate and take account of the physical impacts of climate change that are now locked in because of historic and ongoing emissions.Businesses need to be able to deal with our new and evolving climate reality. This means fully appreciating the physical risks that climate change will bring and taking action to build resilience.